Measurement of the temperature variation along the length of a triple concentric tube heat exchanger - Praveen, Balakrishnan
This final year project is about to deals with the measurement of temperature variation along the length of the heat exchanger for different fluids using T-type thermocouples and Agilent Data Acquisition System.